The role of innovative technologies in improving the efficiency of sports facility construction management - Melnyk , V. (Ways to Improve Construction Efficiency, 2023)
The construction of sports facilities is undergoing dynamic transformation under the influence of innovative technologies. Faced with growing competition, budget constraints, and high quality requirements, companies are forced to seek new solutions to optimize their processes. Modern technologies in construction management significantly improve efficiency, reduce costs, enhance safety, and shorten project timelines. A key driver of innovation is the need to adapt to evolving market demands. Sports facilities for competitions, cultural events, or recreation must meet high standards. Therefore, technologies such as Building Information Modeling (BIM), the Internet of Things (IoT), and automation ensure coordination between all stakeholders, allowing faster and more informed decisions. The growing environmental awareness also shapes modern construction practices. Facilities must be energy-efficient, use sustainable materials, and minimize their environmental footprint. Innovative tools help design and implement such solutions, ensuring compliance with current environmental standards. The integration of digital technologies into construction processes also improves transparency, enabling real-time monitoring and proactive risk management. The main aspects of innovation in construction management, its advantages, challenges, and role in shaping modern infrastructure are explored. The use of advanced technologies not only improves project outcomes but also helps create sustainable, functional spaces that respond to societal needs. As the construction industry evolves, the ability to effectively implement innovations will determine the competitiveness and resilience of companies in the global market. Their successful integration into sports facility projects demonstrates how digitalization is reshaping the future of construction on both strategic and operational levels.